YHWH Ekhad dalam Ulangan 6:4 sebagai Dasar Panggilan Pengajaran Monoteis - Noh Ibrahim Boiliu (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
The issue of Deuteronomy 6:4, which includes the monotheistic creed of Shema Yisrael, is often interpreted solely in the context of monotheistic dogmatics. Deuteronomy 6:4 is not limited to the framework of monotheistic dogma but also has an educational and legal dimension that shapes the moral identity of Israel. This article is an attempt to develop the concept that within the teaching of monotheism lies an effort to form the moral and identity of believers. The article proposes the idea that the call